Experimental studies of the influence of temperature on the process of polystyrene processing in a supercritical water environment - Gilmutdinov Ilnur (EPJ Web of Conferences)
This paper discusses a hydrothermal method for processing polystyrene in a supercritical water environment. This depolymerization process is carried out in a closed reactor where water serves as a solvent, catalyst and reactant. When approaching the critical point, water changes its properties. These significant changes allow supercritical water to cause rapid, selective reactions to convert polystyrene into low molecular weight hydrocarbons. In this work, experimental studies were carried out on the processing of polystyrene in supercritical water at temperatures T = 375 - 425 0C, a volume of water equal to V = 200 ml, for a time τ = 10 - 120 minutes. Hydrothermal processing of polystyrene in supercritical water leads to the formation of a liquid phase, which was analyzed with a Crystal 9000 gas chromatography-mass spectrometer. The analysis results indicate the content of styrene, ethylbenzene, benzene, toluene, and naphthalene in the liquid phase. It was found that at temperature T=375 0C and time τ=10- 15 minutes, a significant amount of styrene is formed. This work also examined the mechanism of depolymerization of polystyrene in supercritical water.